Granulocyte development, tissue recruitment, and function during allergic inflammation - Radtke, Daniel; Vöhringer, David (European Journal of Immunology, 2023)
Granulocytes provide a fast innate response to pathogens and allergens. In allergy and anti-helminth immunity, epithelial cells of damaged barriers release alarmins like IL-25, IL-33, and thymic stromal lymphopoietin (TSLP) but also chemokines like CXCL1 or CCL11 to promote cell recruitment and inflammation. In addition, mast cells positioned at barrier tissue sites also quickly release mediators upon specifically sensing antigens through IgE bound to FcεR1 on their surface. Released mediators induce the recruitment of different granulocytes in a timely ordered manner. First, neutrophils extravasate from the blood vasculature to the side of alarmin release and promote a potent inflammatory response. Alarmins and activated mast cells further promote activation of ILC2s and recruitment of basophils and eosinophils, which inhibit neutrophil recruitment and enhance tissue type 2 immunity. In addition to their potent pro-inflammatory effector functions, granulocytes can also contribute to termination and resolution of inflammation. Here, we summarize the development and tissue recruitment of granulocyte subsets, and describe general effector functions and aspects of their increasingly appreciated role in limiting tissue damage. We further discuss targeting approaches for therapeutic interventions in allergic disorders.
CRIS-Team Scopus Importer:2023-04-21
Keywords: Allergy; Basophils; Eosinophils; Granulocytes; Neutrophils